Corporate Governance in India: Is an Independent Director a Guardian or a Burden? - Arul, P. G. (Prabandhan: Indian Journal of Management, 2010)
The origin of the corporate governance problem lies in the separation of ownership and control in widely held corporations owned by a large number of small and dispersed shareholders who need to delegate the responsibility of running the day to day operations of the corporation to professional managers. Since these shareholders find it costly and lack the incentive to monitor management, managers may behave opportunistically to run the company in their interests rather than the interest of shareholders. The managerial opportunism imposes agency costs manifested in unobservable and often unverifiable actions taken by them such as expanding firm size beyond optimal level, consuming perquisites, or satisfying managerial hubris, all of which increase their private benefits and reduce the value of the firm and also the benefits to the shareholders.The board of directors acts as one of the most important governance mechanisms in aligning the interests of managers and shareholders. The important functions of the board, were laid down in the report on the Financial Aspects of Corporate Governance issued in 1992 by the Cadbury Committee. The committee suggested that the universally accepted principle is that the board of directors act as fiduciaries of shareholders’ and other stakeholders’ interest to execute various functions of the independent directors.